Troubleshooting Cochlear Implant Processors via Tele-Audiology - Boss, Benjamin (Seminars in Hearing, 2021)
This case study examines the methods used to troubleshoot a cochlear implant processor via video visit with a nonagenarian (90+ years old) with a bimodal cochlear implant system. This article will discuss the evaluation and management as well as which specific issues could be addressed virtually and how they were resolved. Examples will be provided about how to virtually connect with the patient and how to best facilitate communication during a video visit. Additionally, this article will examine the captioning apps and other hearing assistive technology available for smartphones that can provide further assistance during a cell phone call along with their benefits and limitations.
Keywords: cochlear implant; telemedicine; bimodal; hearing aid; cell phone